Honour, Fear, and Benefit—In That Order: The Interpolation Of Τιμή in 1.75.3 of Thucydides’ Speech of the Athenians at Sparta - Rusten, Jeffrey S. (Histos, 2024)
The triad of motives for Athenian action in 1.76.2 is preceded at 1.75.3 by the much-quoted listing of the same three items, in a different order and with too many list-markers, both sequential and preferential. Thucydides’ consistent usage of these markers reveals καὶ τιμῆς and μάλιστα μέν to be insertions. The motive for the interpolation of τιμή (to make the first list match the second) is easy to understand, μάλιστα μέν being added to ‘clarify’ the interpolation on the mistaken analogy of 1.32.1. The restored text eliminates the need to locate ‘fear’ in 75.3, since security and benefit are first introduced in 75.4–5 (after ‘honour’ has been highlighted in the Persian war). The final, full list in 1.76.2 reaches back to 1.73.4 to sum up the whole sequence of allegedly exculpatory human motivations—honour, fear, and benefit—behind Athens’ actions.